Protection for Women as A Response of Pregnancy prior to Marriage Phenomenon in Bali - kumala Dewi, Ni Komang Ratih; Yogi Arthani, Ni Luh Gede; Sutrisni, Ni Komang; Pradnyani Dewi, Putu Putri; Purnami Sari, Ni Nyoman Dewi Mega (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 12 No 4 (2023), 2023)
The development of sing beling sing nganten (pro-choice for married by accident) the sing beling sing nganten phenomenon in Bali is causing concern among parents and the community due to the younger generation's inclination towards engaging in sexual relationships before marriage, often with the intention of pregnancy. Various triggering factors lead them to these actions. Women, in particular, may not fully contemplate the repercussions or considerations if their plans go awry. Consequently, there's a need for protective measures for women within this phenomenon. The research aimed to identify the necessary protection for women in response to this phenomenon. Employing empirical and legal research methods, the study utilized oral data from interviews and direct observation of real behaviors. The research identified two forms of protection for women concerning this phenomenon: Preventive Legal Protection and Repressive Legal Protection.